A Change of Accounting Valuation ‒ The Example of IAS 41 "Agriculture" - Grabiński, Konrad (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The main aim of the article is to present IAS 41 "Agriculture" as a sign of evolution in IFRS’s valuation. From a historical point of view, agricultural activity has been based on historical cost accounting. The introduction of IAS 41 "Agriculture" can be considered a revolution where valuation is concerned. The first part of the article outlines the philosophy and detailed regulations of IAS 41. Assumptions of biological asset valuation are then analysed using the example of the timber industry. The final part of the article presents the most controversial aspects of IAS 41, especially where early income recognition is concerned. Additional practical examples are provided, when the fair value of biological assets and agricultural produce and its impact on the income statement generate negative consequences for an entity’s financial statement.